2019
DOI: 10.3390/genes10060411
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Activities of the Saccharomyces cerevisiae Pif1 Helicase Are Regulated by Its N-Terminal Domain

Abstract: : Pif1 family helicases represent a highly conserved class of enzymes involved in multiple aspects of genome maintenance. Many Pif1 helicases are multi-domain proteins, but the functions of their non-helicase domains are poorly understood. Here, we characterized how the N-terminal domain (NTD) of the Saccharomyces cerevisiae Pif1 helicase affects its functions both in vivo and in vitro. Removal of the Pif1 NTD alleviated the toxicity associated with Pif1 overexpression in yeast. Biochemically, the N-terminally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 39 publications
7
31
0
Order By: Relevance
“…The results of these experiments are shown in Figure 1. Here, we recapitulated the toxicity of Pif1 overexpression reported by others [35,36], finding an approximately 50-60% reduction in wild-type growth upon overexpression of the helicase ( Figure 1A).…”
Section: Cellular Acetylation Status Modulates Pif1 Overexpression Tosupporting
confidence: 84%
See 2 more Smart Citations
“…The results of these experiments are shown in Figure 1. Here, we recapitulated the toxicity of Pif1 overexpression reported by others [35,36], finding an approximately 50-60% reduction in wild-type growth upon overexpression of the helicase ( Figure 1A).…”
Section: Cellular Acetylation Status Modulates Pif1 Overexpression Tosupporting
confidence: 84%
“…To understand the impact of global cellular acetylation on the function of Pif1, we initially sought to alter the acetylation dynamics in the cell by creating either KAT or KDAC mutant strains. It has previously been reported that the overexpression of Pif1 in S. cerevisiae is toxic to cell growth [35,36]. Therefore, we used this overexpression toxicity phenomenon to develop a phenotypic assay to determine the impact of cellular acetylation.…”
Section: Cellular Acetylation Status Modulates Pif1 Overexpression Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Lc and Kc did not differ between loci located more than 33kb away from the centromere, the coefficients of diffusion (D) were similar for the 12kb and 33kb centromere proximal loci but significantly increased for loci more than 50kb away from the centromere ( Figure 1G). As previously described, all the loci analysed showed sub-diffusive motion, with mean values for alpha ranging from alpha 12kb =0.36 to alpha 116kb = 0.51 and a large cell-to-cell variation 19,26,34,35,37,38 . As for D, alpha values were low and indistinguishable for the two centromere proximal loci at 12 and 33 kb and significantly higher for loci located beyond 50 kb ( Figure 1H).…”
Section: Differential Centromere and Telomere Mobilitysupporting
confidence: 64%
“…Genome integrity is also highlighted by CBC2, which encodes an RNA binding and processing factor involved in telomere maintenance (LEE-SOETY et al 2012). Hrq1 is known to regulate telomerase activity at both DSBs and telomeres (BOCHMAN et al 2014;NICKENS et al 2018;NICKENS et al 2019). Mutation of the gene encoding the Vps41 vacuolar membrane protein (NAKAMURA et al 1997) also negatively interacted with hrq1-K318A.…”
Section: Hrq1-k318a Interactionsmentioning
confidence: 99%